Antibacterial activity of water and ethanol extract of Allium sativum, Curcuma mangga, and Acorus calamus combination - Bayyinatul Muchtaromah; Mujahidin Ahmad; Romaidi Romaidi; Lina Ainun Nazilah; Nayla Alin Naja (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Madura has been known as an Indonesian tribe that usually used many recipes of traditional medicine in their daily life. One of the medicinal herbs to increase female fertility is the herbal "Subur Kandungan", which consists of garlic (Allium sativum), temu mangga (Curcuma mangga), jeringau (Acorus calamus). The purpose of this study was to determine the phytochemical content and antibacterial activity of A. sativum, C. mangga and A. calamus combination in water and ethanol solvent against Streptococcus aureus and Escherichia coli. There were three kinds of combinations with different composition ie first combination/C1 (36:36:28); second combination/C2 (40:30:30); third combination/C3 (35:40:45). Clindamycin was as a positive control. The phytochemical screening detected triterpenoids in both extracts, while alkaloids, flavonoids only in ethanol extracts. The highest inhibitory zone of both extracts to S. aureus and E. coli were discovered in C3 as strong and moderate inhibition. The most effective MIC value of water extract against S. aureus was found on C3 (9.76 x1010) while ethanol extract was obtained by C1 (5.9x108) at concentrations of 0.39% and MBC at 0.78%. The best MIC value of water extract against E. coli was found on C1 (1.08x1010) at a concentration of 25% and MBC at 50%, whereas ethanol extract was got on C3 (9.7x109) at 0.39% & MBC at 0.78%. It could be concluded that “Subur kandungan” herb recipes could be used as antibacterial drugs, which third combination/C3 in the ethanol solvent is the best treatment compare with others.